Venous Side Branch Ligation as a First Step Treatment for Haemodialysis Access Induced Hand Ischaemia: Effects on Access Flow Volume and Digital Perfusion. Issue 6 (December 2015) - Vaes, R.H.D.; Wouda, R.; Teijink, J.A.W.; Scheltinga, M.R.
Abstract : Objective: Haemodialysis access induced distal ischemia (HAIDI) induced by an autogenous arteriovenous fistula (AVF) is caused by loss of blood pressure somewhere along the arterial blood supply of the arm. In some patients, side branches of the access' venous outflow tract may contribute to this blood pressure loss. Beneficial effects of side branch ligation (SBL) as a first step approach to ischemic symptoms have been reported. However, effects on access flow and AVF function after prolonged follow up are unknown. Materials and methods: Prior to SBL, HAIDI patients with a brachial artery based AVF were studied using a questionnaire quantifying hand ischemia, digital brachial index (DBI, finger plethysmography), and Duplex analysis. Access flow volume, patency rates, hand perfusion, and complications were determined during a 12 month observation period following SBL. Results: In 9 years, SBLs were performed in 20 haemodialysis patients, either as a single operative procedure ( n = 10) or supplemented ( n = 10) with additional surgical techniques during the same procedure (banding, n = 5; basilic vein transposition, n = 4; DRIL, n = 1). Follow up data after 12 months were available in 18 patients. One patient with progressive hand ischemia required access ligation 3 months after SBL. Hand ischemia was attenuated or abolished in the remaining 17 patients (94% clinical success rate). DBI improved from 0.51 ± 0.05 (pre-operative) to 0.68 ± 0.04 (immediate post-operative) and 0.83 ± 0.07 (at 1 year follow up). One year primary, assisted primary, and secondary patency rates were 67% (12/18), 83% (15/18), and 94% (17/18), respectively, while mean access flows remained acceptable at 710 ± 70 mL/min. Conclusions: Ligation of non-functional venous side branches of an autogenous brachial artery AVF causing hand ischemia leads to prolonged attenuation of hand ischemia whereas access flow volumes are maintained after 1 year of follow up. Side branch ligation must be considered prior to embarking on more invasive surgery for HAIDI.